Sitting/lying time is associated with waist‐to‐hip increase but not with body weight increase or blood cardiovascular risk factors changes in adult women living in social vulnerability: A 2‐year longitudinal study. Issue 3 (10th December 2019) - Vieira, Nathalia F. L.; Bueno, Nassib B.; Silva, Sirley M.; Lins, Isabela L.; Albuquerque, Fabiana C.; Macêna, Mateus L.; Silva‐Júnior, André E.; Pureza, Isabele M.; Clemente, Ana G.; Florêncio, Telma T.
Abstract: Objective: The present study aimed to determine whether physical activity and energy intake are associated with the anthropometric and blood cardiovascular risk factors alterations in women living in social vulnerability for a period of 2 years. Methods: The study was carried out with women residing in the outskirts of Maceió‐AL, aged between 19 and 45 years. We characterized the socioeconomic and biochemical profile (glucose, insulin, and blood lipids) at the beginning and at the end of the study. Anthropometric evaluation was performed in three moments: at the beginning, and after 1 and 2 years of follow‐up. Energy expenditure, measured by doubly labeled water, physical activity, measured by 7‐day triaxial accelerometry, and energy intake, measured by 3‐day 24‐hour food recall, were collected at baseline. Results: After 2 years, 34 women were completely assessed, with a mean age of 33.7 years. Women spent around 16 hours of the day sitting/lying down. There was an increase in body weight (from 64.61 ± 11.69 to 66.37 ± 13.26 kg, P  < .01), which was not associated with any of the predictors. There was also an increase in waist/hip ratio (WHR) (from 0.84 ± 0.07 to 0.87 ± 0.05, P  < .01), which was positively associated with the amount of sitting/lying time per day. There were no significant alterations in blood cardiovascular risk factors. Conclusion: Energy intake did not predict anthropometrical changes. Sitting/lying time was associated with an increase in WHR, but not in body weight or blood cardiovascular risk factors in low‐income women.